Transporte de larvas de jundiá Rhamdia quelen (Quoy & Gaimard, 1824) em sacos plásticos - SILVA, Rodrigo Aguiar da (2015)
This work aimed to evaluate the effects of density and confinement time in the survivability of silver catfish larvae (Rhamdiaquelen) to the simulation of transport. The work was comprised by five trials that evaluated the conditions to transport larvae in different densities and periods of transport. The transportation was just simulated, the larvae were hosted into plastic bags that were kept static, and maintained in trays that were being supplied by a recirculation system. In the first trial was measured the transportation time for larvae of just 24 hours post-hatching (24 HPH). The second trial measured the density factor on larvae transport. In the third trial was also evaluated the period of transport, but at density 45.000 (Larvas.L-1) and temperature of 20°C. The fourth trial also measured different densities, but at 20°C, and the fifth and last trial measured the transporting time for more developed larvae at density 4.000 (Larvas.L-1). The results demonstrate that silver catfish larvae can be already conveyed even before they present active movement. The transportation can be held at high densities, up to 45.000 Larvae.L-1, when at 20°C. The larvae of 48 HPH at 25°C can be transported at 23°C for 12 hours at densities up to 8000 Larvae.L-1, with no survival loss. Larvae with 120 HPH at 25°C can be transported at densities of 4000 Larvae.L-1 at 23°C for even 36 hours without significant mortality as result of the transport.